2021
DOI: 10.3390/healthcare9121629
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Observation and Motivation (MOM) Program with m-Health Support on Maternal and Newborn Health

Abstract: Maternal and child nutrition has been a critical component of health, sustainable development, and progress in low- and middle-income countries (LMIC). While a decrement in maternal mortality is an important indicator, simply surviving pregnancy and childbirth does not imply better maternal health. One of the fundamental obligations of nations under international human rights law is to enable women to endure pregnancy and delivery as an aspect of their enjoyment of reproductive and sexual health and rights and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…More generally, though, the limits of an SMS-based approach in improving MNCH indicators in this setting are clear from the lack of improvements in some outcomes, such as awareness of swelling and convulsions as danger signs, DHA as an important supplement during pregnancy, and knowledge of blood type [9,21]. Evidence suggests that multipronged approaches that involve messages, reminders, and coaching sessions that enabling health workers to support women, together with in-person education [10], have the potential to have a greater effect on MNCH-related behaviour change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, though, the limits of an SMS-based approach in improving MNCH indicators in this setting are clear from the lack of improvements in some outcomes, such as awareness of swelling and convulsions as danger signs, DHA as an important supplement during pregnancy, and knowledge of blood type [9,21]. Evidence suggests that multipronged approaches that involve messages, reminders, and coaching sessions that enabling health workers to support women, together with in-person education [10], have the potential to have a greater effect on MNCH-related behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…The previous results of the impact of mHealth interventions on MNCH in low-and middle-income countries (LMICs) reveal that mHealth interventions are effective at improving various MNCH outcomes such as increased utilisation of antenatal and postnatal care (PNC) services, use of skilled birth attendance, immunisation, iron supplementation, and exclusive breastfeeding [7,10,[24][25][26][27][28][29]. Mbuthia et al (2019) [30], in their systematic review of the impact of mHealth-based interventions on PNC in rural settings, found that SMS-based messaging can positively influence attitudes, norms, skills, and self-efficacy among mothers and address environmental barriers that hinder the uptake of PNC in rural areas [30].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies available showed mHealth application alone produced better health outcomes than routine standard care 86–91. Similarly, mHealth apps integrating with healthcare professional’s guidance promoted better health outcome compared with routine care alone 92 93. Meanwhile, it is evident that mHealth application among community dwellers have limited use without the interaction with healthcare team 94 95.…”
Section: Introductionmentioning
confidence: 99%